Decolonial Spectatorship and Performances of Contemporary Dance in South Africa:Mamela Nyamza’s Choreographies of Embodied Politics of Race and Gender in Place - Sarah DAVIES CORDOVA (E-REA)
The struggles for dance spaces, for festivals, for recognition of the dancers have long undergirded contemporary dance in Africa in general and no less so in postapartheid and covid-controlled South Africa where governmental institutional structures refuse to prioritise the arts sector and particularly independent dance practitioners despite the unique role they hold in the public space with performances embodying activist politics of race, gender and place. Focusing on artist-activist Mamela Nyamza, what follows takes in the various locations of her culture of activism: in and on the body; in relation to perpetrated violence in gender and race relations; in displays of counter-dance in public places and with Black [women’s] bodies on stage; in institutionalised seats of power. It traces her decolonial choreographic practice that layers personal and socio-political issues into distinctive artistic expressions and intellectual exercises for her audiences. Performed through de-centered corporeal positionalities and dance vocabularies that carry her conceptual signature use of words, cloth and clothes, everyday objects, and spaces, moving and flexing across dance genres, language paradigms, relational exchanges, her works call out the violence and wounds that injustices perpetuate by challenging representations of women, human relations and race and gender positionalities in place, historically and within postapartheid South Africa and beyond.